Formal techniques for safety-critical systems : 7th International Workshop, FTSCS 2019, Shenzhen, China, November 9, 2019, Revised selected papers /: 7th International Workshop, FTSCS 2019, Shenzhen, China, November 9, 2019, Revised selected papers. (2020) - Unknown
No abstract available